2005
DOI: 10.1111/j.0030-1299.2005.14056.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in ecological stoichiometry: insights for population and community ecology

Abstract: T. 2005. Recent advances in ecological stoichiometry: insights for population and community ecology. Á/ Oikos 109: 29 Á/39.Conventional theories of population and community dynamics are based on a single currency such as number of individuals, biomass, carbon or energy. However, organisms are constructed of multiple elements and often require them (in particular carbon, phosphorus and nitrogen) in different ratios than provided by their resources; this mismatch may constrain the net transfer of energy and elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
161
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(166 citation statements)
references
References 111 publications
1
161
1
3
Order By: Relevance
“…In fact, nitrogen deposition could promote plant diversity, because rare species are favoured under phosphorus-limited conditions 29 . The relationship between N:P stoichiometry and species diversity 30 is, moreover, not necessarily linear. For instance, Sasaki et al 25 have shown unimodal relationships between N:P stoichiometry and species richness in terrestrial ecosystems that reach a maximum at B20 biomass N:P ratio, that is, at a much lower ratio than current deposition ratios 4 .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In fact, nitrogen deposition could promote plant diversity, because rare species are favoured under phosphorus-limited conditions 29 . The relationship between N:P stoichiometry and species diversity 30 is, moreover, not necessarily linear. For instance, Sasaki et al 25 have shown unimodal relationships between N:P stoichiometry and species richness in terrestrial ecosystems that reach a maximum at B20 biomass N:P ratio, that is, at a much lower ratio than current deposition ratios 4 .…”
Section: Resultsmentioning
confidence: 98%
“…For instance, Sasaki et al 25 have shown unimodal relationships between N:P stoichiometry and species richness in terrestrial ecosystems that reach a maximum at B20 biomass N:P ratio, that is, at a much lower ratio than current deposition ratios 4 . Several important ecosystem processes such as the energy and element transfers through trophic levels have also been related to these changes in organism's N:P ratios 30 (Fig. 4) (see details in Supplementary Tables S1-S18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ecosystem function beyond the ''who-eats-whom'' of food-web dynamics is important to food-web studies (Moorcroft, 2003;Pascual, 2005) and potentially, as in the context of our work, to species persistence. While studies including biogeochemical considerations and ecological stoichiometric constraints (DeAngelis, 1992;Elser et al, 1998;Moe et al, 2005;Schlesinger, 1997;Sterner and Elser, 2002) do place organisms in dynamic physical-chemical environments, effects on multiple trophic level food-web dynamics are not typically addressed: small, often analytically tractable, systems are in focus (Daufresne and Loreau, 2001a, b;Grover, 2003;Hall et al, 2006;Kuijper et al, 2004;Loladze et al, 2004). We still lack a basic understanding of how environmental feedbacks impact the dynamics and persistence of structurally realistic food webs.…”
Section: Introductionmentioning
confidence: 99%